2001 IEEE Ultrasonics Symposium. Proceedings. An International Symposium (Cat. No.01CH37263)
DOI: 10.1109/ultsym.2001.991618
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid surface-bulk mode in periodic gratings

Abstract: We report on a SAW/BAW hybrid mode (SBH), which arises from surface skimming bulk wave due to the trapping of its energy by a counter-propagating surface wave (SAW) or leaky surface wave (LSAW), in periodic grating structures. The SBH is the result of an interaction between surface and bulk waves and exists within limited frequency region, outside which it is decomposed into counterpropagating SAW and BAW. Different examples of SBH mode illustrate interactions of BAW with pure SAW, leaky and high-velocity leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The majority of the energy is confined within the IDT and reflector gratings [ 30 ]. This spurious response is generated by the anomalous dispersion due to BAW backscattering [ 31 , 32 ]. We can cut the total energy confined in the IDT by reducing the standing waves due to reflection from the reflector gratings.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The majority of the energy is confined within the IDT and reflector gratings [ 30 ]. This spurious response is generated by the anomalous dispersion due to BAW backscattering [ 31 , 32 ]. We can cut the total energy confined in the IDT by reducing the standing waves due to reflection from the reflector gratings.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…From (1) it follows that at the cut-off frequency, ∆=∆ B , the function ν(∆) shows a pole. It is consistent with the behavior of SSBW when the latter exhibits the properties of exceptional bulk wave, as, for example, SH waves propagating in rotated Y-cuts of quartz, 90°-propagation.…”
Section: Approximation Of Ssbw Effect Of Harmonic Admittancementioning
confidence: 99%
“…Recently, it was found that in some substrates SSBW builds a surface-bulk hybrid mode (SBH) with SAW or leaky wave [1][2]. It results in parasitic resonances and general deterioration of SAW filter performance.…”
Section: Introductionmentioning
confidence: 99%